Enaminone formation drives the coupling of biosynthetic pathways to generate cyclic lipopeptides - Candra, Hartono (2022)
A family of novel cyclic lipopeptides named tasikamides A H (Tsk A H) were discovered recently in Streptomyces tasikensis P46. Aside from the unique cyclic pentapeptide scaffold shared by the tasikamides, Tsk A C contain a hydrazone bridge that connects the cyclic pentapeptide to the lipophilic alkyl 5- hydroxylanthranilate (AHA) moiety. Here we report the production of tasikamides I K (Tsk I K) by a mutant strain of S. tasikensis P46 that overexpresses two pathway-specific transcription regulators. Unlike Tsk A C, Tsk I K feature a rare enaminone-bridge that links the cyclic peptide scaffold to the AHA moiety. Our experimental data suggest that Tsk I K are generated by the coupling of two biosynthetic pathways via a nonenzymatic condensation reaction between an arylamine and a β-keto aldehyde-containing precursor. The results underscore the nucleophilic and electrophilic reactivity of the β-keto aldehyde moiety and its ability to